Human Resource Management in the Context of the Global Economic Crisis - Buley, Natal'ya V.; Demchenko, Tatiana S.; Makushkin, Sergey A.; Vinichenko, Mikhail V.; Melnichuk, Aleksandr V. (International Journal of Economics and Financial Issues, 2016)
The relevance of the study of human resources management in crisis conditions is determined, firstly, during social change, destroyed the existing usual ways of living, changing values and priorities of society, leading to the disappearance of some and the emergence of other forms of activity. This puts a person a new life task, “creativity” as a manifestation of activity of subject of activity, when the subject and object of the interaction may be reversed, as the operand and the operator. It should be stressed that in modern conditions of dynamic change is changing the paradigm, the subject and methods of management. And, as shows the analysis of the literature, which is especially valuable for economic psychology, psychology of business and management - namely inadequate representation of managers about changes in the economic, political, juridical (legal) entities and the management are the major obstacle to business development and the formulation of effective management of the organization. The problem of the inadequacy of the views of managers about the realities on the basis of which develops business or management is particularly acute for the Russian economy. Keywords: economy, economic crisis, human resources, management, motivation JEL Classifications: J22, J24, J31, J38